Knowledge Economy in a Globalised India: Who Gets What? - June Cahyaningtyas (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2015)
At the beginning of the 21st century, the world started to spot India as one ofthe global epicenter of Information Technology (IT) industry. Unlike any otherindustries, IT caters the idea of knowledge and market, two essential pillars inthe knowledge economy. Also, unlike the old type of financial economy whichtends to be excessive due to its weighting on growth development, the termknowledge economy brings the idea of human capital investment and greateropportunity for vertical mobilization, hence promises more social equity.However, despite a more positive outlook towards India, records on poverty,malnutrition, and other social issues in India seem unmoved. This paperattempts to highlight how IT industry has actually developed in India and howlikely it will lead to.